Flagging difference: Identification and emotional responses to national flags. Issue 5 (27th February 2020) - Muldoon, Orla T.; Trew, Karen; Devine, Paula
Abstract: Flags can be thought of as representations designed to unite the national community. Emotional responses are seen as being particularly important in driving allegiances to flags. In societies affected by conflict, where the nation itself is contested, emotional responses to national symbols however, have the potential to be divisive. In this study, using a large scale sample in Northern Ireland, emotional responses to the in‐group and out‐group flags and their relationship to national identities are considered. 1, 179 respondents reported their self‐categorized national identity, as well as explicit emotional responses to both in‐group and out‐group flags. The strength of identification with preferred national group, British, Irish, or Northern Irish, was also measured. Emotional responses to in‐group flags were significantly related to both strength of national identification and the type of emotion, annoyed, hopeful, satisfied, or uneasy, under consideration. Weaker emotional responses and different emotions were reported in response to out‐group flags. The results of the study are interpreted as consistent with appraisal and intergroup emotions theory which suggests the strongest emotional responses are evidenced in response to symbols of one's own group. The importance of emotions to understanding the dynamics of intergroup conflict, and in Northern Ireland in particular, is also discussed.